Detenidos políticos en la Prisión Provincial de Huelva : conclusiones y estudio de series / Juan José Antequera Luengo, Juan José Luengo Jiménez - Luengo Jiménez, Juan José; Antequera Luengo, Juan J.
Contiene: [1].(1936) -- [2]. (1937).